A simple and fast method for Named Entity context extraction from patents. (1st December 2021) - Puccetti, Giovanni; Chiarello, Filippo; Fantoni, Gualtiero
Abstract: The process of extracting relevant technical information from patents or technical literature is as valuable as it is challenging. It deals with highly relevant information extraction from a corpus of documents with particular structure, and a mix of technical and legal jargon. Patents are the wider free source of technical information where homogeneous entities can be found. From a technical perspective the approaches refer to Named Entity Recognition (NER) and make use of Machine Learning techniques for Natural Language Processing (NLP). However, due to the large amount of data, to the complexity of the lexicon, the peculiarity of the structure and the scarcity of the examples to be used to feed the machine learning system, new approaches should be studied. NER methods are increasing their performances in many contexts, but a gap still exists when dealing with technical documentation. The aim of this work is to create an automatic training sets for NER systems by exploiting the nature and structure of patents, an open and massive source of technical documentation. In particular, we focus on collecting the context where users of the invention appear within patents. We then measure to which extent we achieve our goal and discuss how much our method is generalizable to other entities and documents. Highlights: Patents are a rich source of information unavailable elsewhere though hard to recover systematically. Natural Language Processing allows the extraction of large amounts of detailed knowledge from patents. A simple methodology for data-set creation and user context extraction deployed on patents text. Expert systems can build user context extraction for collection and analysis of this entity.